Manipulation of Light Environment to Produce High-quality Poinsettia Plants - Mata, Diego Alejandro (2009)
The phytochromes, a family of photoreceptors which maximally absorb red (R) and Far-red (FR) light, play an important role defining plant the architecture of the plant and consequently its value in the market. In this work we evaluated the manipulation of light quality as an alternative to the use of plant growth regulators (PGR) in order to produce poinsettia plants (Euphorbia pulcherrima Willd. ex Klotzsch) without affecting commercial parameters of the product. Poinsettia ‘Freedom Red’ plants were cultivated in two different light environments characterized by different R/FR ratios = 5.7 and 1.1 in combination with or without one application of PGR. We used a photoselective film that significantly reduced the FR component of the light or a transparent film to obtain different R/FR ratios. Plants cultivated under high R/FR ratio were shorter and more compact than those grown under transparent film. Other quality characters like bract and leaf area, dry weight, stem diameter, number of lateral branches and plant width did not differ significantly between light treatments. Flowering time was slightly delayed in plants grown under high R/FR ratio compared with those cultivated under control treatment. Additive effects were detected between light and PGR factors indicating that the manipulation of the light is an alternative strategy to reduce or replace the use of PGR in commercial production systems that usually require several PGR applications.